TINJAUAN KEEFEKTIFAN SISTEM GEOSINTETIK DIANGKUR SEBAGAI METODA PERKUATAN LERENG MELALUI UJI LAPANGAN DAN UJI MODEL LABORATORIUM - H. , Abdurrachman
Landslide problems on soil slopes occur frequently in Indonesia and cause large amount of losses. Based upon available record from The Directorate of Environmental Geology, the occurrence and the losses caused by landslide increase from year to year. Naturally, down slope movement of a soil mass is retained by the shear strength of its forming material. For unstable slopes with low shear strength, several slope stabilization methods have been developed. One of the slope stabilization methods is The Anchored Geosynthetic System (AGS) proposed by Robert Koerner (1986). AGS can be used to stabilize either natural slopes or engineered slopes by covering the slope with geosynthetic followed by driving some ground anchors up to specified depth beyond the failure surface. As a new slope stabilization method, the effectiveness of AGS has to be examined. Accordingly, this study consists of: field test to observe the effectiveness of AGS application in natural slope, laboratory model test to observe the effectiveness of AGS application in embankment slope, and failure simulation using Plaxis Program to obtain the failure surface on embankment slope reinforced by AGS. In field test, monitoring results from the installed instruments indicate that the application of AGS is able to reduce the movement during rainy season up to 60 % of the movement before AGS installation. The laboratory model test result indicates that the shape of failure surface is logarithmic spiral passing the toe of the slope. The shape of the failure surfaces as indicated by the results of failure simulation using Plaxis Program are also logarithmic spiral that close to the shape of the failure surface indicated by the laboratory model test. Different location of the failure surface produces different area of the active zone, where the areas of active zone produced by Plaxis Program are larger range from 12 % to 22 % than the area of active zone produced by the laboratory model test.